Reliability analysis of hydrogen storage composite pressure vessel with two types of random-interval uncertainties - Li, Wenbo; Zhang, Leiqi; Lv, Hong; Zhang, Lijun; Liu, Min; Zhang, Cunman; He, Pengfei (International journal of hydrogen energy, 2023)
Due to the uncertainty of structure and material parameters, reliability analysis of hydrogen storage composite pressure vessel (CPV) is an important issue. In this paper, reliability analysis of hydrogen storage CPV is carried out based on kriging surrogate model with two types of random-interval uncertainties. First, progressive failure behavior is analyzed based on finite element model (FEM) of CPV. Second, the kriging model is built to surrogate the burst pressure. Then, global sensitivity analysis is conducted using Sobol method. Finally, uncertainty analysis and reliability analysis of CPV are carried out with two types of random-interval uncertainties. The results show that longitudinal tensile strength, thicknesses of the hoop layers and the helical layers are important factors of the CPV burst. Besides, the reliability of CPV is low (0.048) with random-interval uncertainties, which should be improved to increase the safety of CPV. The proposed method provides a general solution to the reliability analysis of CPV with two types of random-interval uncertainties, which would co-exist in the hydrogen storage CPV. [Display omitted] •The kriging model of hydrogen storage vessel burst is established and verified.•The global sensitivity analysis of burst is carried out by Sobol method.•Longitudinal tensile strength and layer thickness are important influencing factors.•Reliability analysis is carried out with random-interval uncertainties.•Reliability is smaller with hybrid uncertainties than with only random uncertainty.